2004
DOI: 10.1111/j.0009-9163.2004.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of APOAV polymorphisms (T‐1131>C and S19>W) on plasma triglyceride levels and risk of myocardial infarction

Abstract: The importance of an APOAV gene for plasma triglyceride level determination has been shown on transgenic and knockout mice. We examined whether APOAV variants are associated with plasma triglyceride levels and risk of myocardial infarction (MI). We have evaluated the influence of APOAV polymorphisms (T-1131>C and S19>W) on plasma triglycerides in 1191 males and 1368 females representatively selected from the Czech population. Triglycerides have been analysed in 1997 and 2001. Subsequently, we have analysed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 18 publications
9
80
4
Order By: Relevance
“…However, associations of the T allele of the XmnI polymorphism with increased TG, total cholesterol, and LDL-C levels have been described (Dallinga-Thie et al, 1996;Hong et al, 1997). Regarding the S19W polymorphism, the G allele has been associated with higher plasma TG in several populations (Hubacek et al, 2004;Martinelli et al, 2007), as well as in another population from the South Brazil region (de Andrade et al, 2011). These controversial findings may be due to the heterogeneity of the study populations and to their different ethnic backgrounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, associations of the T allele of the XmnI polymorphism with increased TG, total cholesterol, and LDL-C levels have been described (Dallinga-Thie et al, 1996;Hong et al, 1997). Regarding the S19W polymorphism, the G allele has been associated with higher plasma TG in several populations (Hubacek et al, 2004;Martinelli et al, 2007), as well as in another population from the South Brazil region (de Andrade et al, 2011). These controversial findings may be due to the heterogeneity of the study populations and to their different ethnic backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…APOA5, another apolipoprotein, has been reported to be an important regulator of TG levels (Hubacek et al, 2004). Polymorphisms in APOA1 and APOA5 genes have been associated with lipid alterations and CVD (Hubacek et al, 2004;de Andrade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We also performed a cumulative meta-analysis to identify the influence of the initial study on the subsequent publications. The influential role of the study of Bi et al (11) was obvious in the cumulative random effects meta-analysis under the recessive genetic model, and the study of Hubacek et al (27) was obvious under the dominant genetic model (Table 3). …”
Section: Main Results Sensitivity and Cumulative Analysesmentioning
confidence: 99%
“…The -1131T>C polymorphism is located in the promoter polymorphism and risk of CAD were selected in this meta-analysis with 5,050 cases and 7,272 controls (11,12,14,16,17,(26)(27)(28)(29)(30)(31)(32)(33). For the S19W APOA5 gene polymorphisms, 5 studies were included in the metaanalysis with 2,196 cases and 3,933 controls (14,16,17,27,34). Characteristics of included studies are summarized in Table 1 and Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…5,42 A previous study in Caucasians reports that the minor allele frequency of SNP rs662799 was significantly higher among coronary artery disease patients than among controls (OR¼1.98, 95% CI: 1.14-3.48). 43 Another study 44 found that homozygotes of the minor allele frequency of at least one of the SNPs rs662799 and/or rs3135506 were more prone to MI (Po0.001), but they failed to detect significantly different distributions of the ApoA5 genotype between MI patients and controls. In contrast, two prospective studies, which were branch investigations of the NPHS II study 40 and LOCAT study, 34 did not observe any positive association between SNP rs662799 and coronary artery disease.…”
Section: Snps/haplotypes and Plasma Tg Concentrationmentioning
confidence: 99%